What pension policy lessons could Colombia draw from New Zealand? (2020)
The article addresses the feasibility that a less developed country, such as, Colombia might adopt a universal policy scheme, such as, the one that functions successfully in a developed nation, specifically, the one in New Zealand. Starting in the 19th century, the pension schemes in Colombia, and in New Zealand, were designed differently, and have resulted in different outcomes. I conclude that there are several factors, such as, geographic proximity pattern, ageing population, financial sustainability, and superannuation pillar design that would enable Colombia to adopt the first pension pillar successfully. Even so, there are also some challenges, such as, policy legacy, simplicity, pensionable age, institutional weakness, population size, and homeland security that Colombia will need to address to ensure its success – specifically how to decrease poverty among the elderly population without affecting the long-term sustainability of the retirement system.